2019
DOI: 10.6007/ijarped/v8-i3/6213
|View full text |Cite
|
Sign up to set email alerts
|

The Moderating Effect of the CEO Duality towards the Influence of the Ownership Structure on the Firm Performance among Jordanian Public Shareholders Companies

Abstract: Previous studies that dealt with corporate governance mechanisms have testified high significant that created some new direction. The current study aims to be engaged in such trends through investigating the relationship between ownership structure as one of the corporate governance mechanisms and performance of the firm with the presence of moderating variable which is CEO duality in developing countries such as Jordan. This study used the panel data method to analyze data for a sample of 180 companies listed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…The frequency of meetings had a positive relationship with the probability of distress ( Khurshid et al, 2018 ). Various studies ( Al-Musali and Ismail, 2015 ; Dakhlallh et al, 2019 ; Bendig et al, 2020 ; Al-Qatanani and Siam, 2021 ) highlighted the moderating role of the board from various perspectives of the firm. An effective board is expected to avoid politics and enhance managerial accountability to safeguard the interests of key stakeholders.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…The frequency of meetings had a positive relationship with the probability of distress ( Khurshid et al, 2018 ). Various studies ( Al-Musali and Ismail, 2015 ; Dakhlallh et al, 2019 ; Bendig et al, 2020 ; Al-Qatanani and Siam, 2021 ) highlighted the moderating role of the board from various perspectives of the firm. An effective board is expected to avoid politics and enhance managerial accountability to safeguard the interests of key stakeholders.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…If the board is not independent, the CEO may exert influence over the board's decision on determining the CEO's compensation package. Dakhlallh et al (2019), state that the link between management ownership, government ownership, and business performance is adversely affected by CEO duality. The study implies that duality might have a negative effect on a firm's performance.…”
Section: Ceo Duality and Financial Performancementioning
confidence: 99%
“…Social corporate responsibilities (CSR) also has a positive effect on the financial performance of an organization because it improves the efficiency of the organization not only in terms of social and environmental concerns but also with achieving the high performance goals of the organization. In many previous studies it was revealed that banking is highly affected by shareholders (Farrukh et al, 2017;Dakhlallh et al, 2019). They also enhance the efficiency to achieve the goal of maximization of shareholders' wealth (Beck et al, 2018).…”
Section: Introductionmentioning
confidence: 99%